Stedman's Bergey's bacteria words - John G. Holt; editor-in-chief
Part of a series of speciality medical word books, this text lists terms related to bacteria: procedures, techniques, abbreviations, drugs, test and equipment names, as well as jargon and other variants. The series is fully cross-indexed and lists phrases as they are heard as well as by main noun